Analisis Kebangkrutan Dengan Menggunakan Model Grover Pada Perusahaan Jasa Sub Sektor Perdagangan Eceran Periode 2015-2020 di Bursa Efek Indonesia - Sri Septi Rahayu; Seflidiana Roza; Ida Nirwana (Journal of Creative Student Research, 2023)
This study aims to determine the potential for bankruptcy using the grover method (G-Score) in Retail Trading Sub-Sector Service Companies listed on the Indonesia Stock Exchange in 2015-2020. The research method used is a quantitative method. The population and sample of this research are 27 Retail Trade Sub-Sector Service companies listed on the Indonesia Stock Exchange for the 2015-2020 period. This research sample selection method used purposive sampling method with a total of 16 companies that met the criteria. The analysis technique in this study uses the Microsoft Exel program in performing calculations using the grover model to predict company bankruptcy. Grover categorizes the company in bankruptcy with a score less than or equal to (-0.02). While the value for companies that are not bankrupt is more or equal to (0.01). Based on Grover's calculations (G-Score) from 16 Retail Trade Service Sub-Sector companies studied from 2015-2020, there were 5 companies that went bankrupt in a given year.